A Mechanically Actuating Carbon‐Nanotube Fiber in Response to Water and Moisture. Issue 49 (13th October 2015) - He, Sisi; Chen, Peining; Qiu, Longbin; Wang, Bingjie; Sun, Xuemei; Xu, Yifan; Peng, Huisheng
Abstract: A new family of hierarchically helical carbon‐nanotube fibers with many nano‐ and micro‐scale channels has been synthesized. They demonstrate remarkable mechanical actuations in response to water and moisture. The water or moisture is first rapidly transported through the trunk micron‐scale channels and then efficiently infiltrates into the interconnected capillary nanoscale channels, similar to the blood flow in our body. Therefore, rapid and large contraction and rotation of the fiber occurs with a high reversibility. These mechanically actuating fibers are promising for various applications, and smart windows and louvers have been investigated as two demonstrations. Abstract : Water lot of twisting : Hydrophilic, hierarchically helical carbon‐nanotube fibers are synthesized. In response to water and moisture they rapidly contract and rotate. The large numbers of nano‐ and micron‐scale channels are responsible for these moisture‐sensing properties. The fibers are lightweight, flexible, and strong, making them suitable for applications, such as smart switches, actuators, robots, and biomimetic devices.